Evaluation of short-chain-length polyhydroxyalkanoate accumulation in Bacillus aryabhattai - Balakrishna Pillai, Aneesh (Braz J Microbiol, 2017)
This study was focused on the polyhydroxybutyrate (PHB) accumulation property of Bacillus aryabhattai isolated from environment. Twenty-four polyhydroxyalkanoate (PHA) producers were screened out from sixty-two environmental bacterial isolates based on Sudan Black B colony staining. Based on their PHA accumulation property, six promising isolates were further screened out. The most productive isolate PHB10 was identified as B. aryabhattai PHB10. The polymer production maxima were 3.264 g/L, 2.181 g/L, 1.47 g/L, 1.742 g/L and 1.786 g/L in glucose, fructose, maltose, starch and glycerol respectively. The bacterial culture reached its stationary and declining phases at 18 h and 21 h respectively and indicated growth-associated PHB production. Nuclear Magnetic Resonance (NMR) spectra confirmed the material as PHB. The material has thermal stability between 30 and 140 °C, melting point at 170 °C and maximum thermal degradation at 287 °C. The molecular weight and poly dispersion index of the polymer were found as 199.7 kDa and 2.67 respectively. The bacterium B. aryabhattai accumulating PHB up to 75% of cell dry mass utilizing various carbon sources is a potential candidate for large scale production of bacterial polyhydroxybutyrate.